Critique of Nasr Hamed Abu Zaid’s Approach to Scientific Interpretation Based on Ayatollah Ma'rifat’s View - Hossein Alavi Mehr; Abdollah Jebreili Jelodar (آموزه‌های قرآنی)
There are different views and approaches to scientific interpretation, its terms and conditions, and many factors have contributed to these differences, but one of the most important is the interpreters’ view of the place of science in understanding the Qur'an so that among some neo-Mu'tazilah, like Nasr Hamed Abu Zaid, as a result of current time and scientific developments has been given a new look at interaction with the Qur'an; Because the awareness of the successful development of the West forced them to reconcile religion and modernity with the motivation of contemplation, and intended to take a scientific approach to the interpretation of Qur'anic verses. Hence, among these scholars, considering that their approach to scientific interpretation is incorrect, Scholars have interpreted many verses of the Qur'an that the Qur'an accepted from the culture of the time and had the meanings of the Qur'an and the Qur'anic history and the standards of interpretation of the Qur'an were not practically observed, but they still had the claim of reflection and scientific interpretation. By looking at their works and thoughts, we find that these kinds of interpretations have both basic and eternal damage as well as methodological damages. But Ayatollah al-Ma'rifat while considers scientific interpretation leads to better understanding of scientific verses but the criteria for scientific interpretation must be observed, and he has always emphasized that definitive science must be used and by being far from the misplaced interpretations of Qur'anic commentary, we avoid the damages of scientific interpretation. In this essay, we criticize Nasr Hamed Abu Zaid’s viewpoint by comparative surveying Ayatollah Ma'rifat’s views.